TRANSIENT EXPRESSION OF REPORTER GENES IN CULTIVARS OF Amaranthus caudatus L - Yaroshko, O. M. (Biotechnologia acta, 2021)
Local cultivars of A. caudatus: Helios and Karmin were used as plant material. Amaranth is a new pseudocereal introduced in Ukraine. The plant biomass of amaranth is used in medicine, food industry and cosmetology industry. Aim. The purpose of the work was to identify the optimal conditions for the transient expression of reporter genes in Amaranthus caudatus cultivars. Methods. Biochemical and microscopy methods were used in the following work. Seedlings and adult plants of different age were infiltrated with agrobacterial suspensions separately (genetic vector pCBV19 with a uidA gene and genetic vector pNMD2501 with a gfp gene in Agrobacterium tumefaciens GV3101 strain). Results. Transient expression of the uidA and gfp genes was obtained in amaranth plants after conduction series of experiments. The most intensive transient expression of gfp and uidA genes was observed in seedlings infiltrated at the age of 1 day. The maximum fluorescence of the GFP protein was observed on 5th–6th days. Conclusions. It was shown that the cultivar Helios was more susceptible to agrobacterial infection than the cultivar Karmin. The effectiveness of Agrobacterium mediated transformation was from 16% to 95% for the Helios cultivar and from 12% to 93% for the Karmin cultivar. The obtained results indicate that the studied amaranth cultivars can potentially be used for obtaining transient expression of target genes and synthesizing target proteins in their tissues in the future.